Role of Glutathionylation in Infection and Inflammation - Checconi, Paola (Nutrients, 2019)
Glutathionylation, that is, the formation of mixed disulfides between protein cysteines and glutathione (GSH) cysteines, is a reversible post-translational modification catalyzed by different cellular oxidoreductases, by which the redox state of the cell modulates protein function. So far, most studies on the identification of glutathionylated proteins have focused on cellular proteins, including proteins involved in host response to infection, but there is a growing number of reports showing that microbial proteins also undergo glutathionylation, with modification of their characteristics and functions. In the present review, we highlight the signaling role of GSH through glutathionylation, particularly focusing on microbial (viral and bacterial) glutathionylated proteins (GSSPs) and host GSSPs involved in the immune/inflammatory response to infection; moreover, we discuss the biological role of the process in microbial infections and related host responses.